Comparision of speed and endurance between short and long distance runner of Kashmir Division - Dar, Nazir Ahmad (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2021)
The main idea and aim of this comparative study is to assess and compare the speed and endurance among long distance and short distance athletes of Kashmir division. For this comparative study (60) subjects were selected, 30 athletes were long distance runner and 30 were short distance runner all were selected from Kashmir division city which were selected randomly from various disticte of Kashmir division for the study. The the statistical criteria used for selecting the subjects was through simple random sampling. All the athletes from both the categories were of the age ranged between 25-35 years. To compare and analyze the speed and endurance among long distance and short distance athletes of Kashmir division. Of the athletes of both the groups two different tests or equipments were used. For speed A digital Stop watch for recording the distance covered per unit time and for endurance Heart Rate count. Vo2max. Bench for Cardiovascular was used. The comparison analysis of data was done by using statistical technique ‘t’- test for finding the significance difference speed and endurance of long and short distance runner of Kashmir division the level of significance was set at 0.05 levels (p<0.05). The calculated means and standard deviation of speed and endurance of long distance distance athletes of Kashmir division selected variables of industrial inhabitants viz. speed( 12.82 ± 1.07 endurance VO2 Max is ( 58.24 ± 7.25 ) and the findings means and standard deviation of selected variables of short distance atheletes of Kashmir division in speed (13.87± 2.93), endurance (448 ± 66.39), Hence the Non-industrial inhabitants were found with sound cardio respiratory capacities as compared to Industrial Inhabitants the difference might be due to the pollution of industries which directly or indirectly affects the population (people) residing in industrial area.